How Do Cultural Differences Between Countries Affect Management Approaches, Ethical Decision-Making Processes and Organizational Culture? - Zeynep Kaptan (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
With globalization, businesses operate in different cultural contexts, and this directly affects management approaches, ethical decision-making processes, and organizational culture. This study aims to examine the effects of cultural differences on the relationship between management approaches, ethical decision-making processes, and organizational culture. In the study, bibliometric analysis method was used to determine which countries are influential in the relevant literature in order to examine cultural differences between countries. The findings show that cultural factors are decisive on leadership and ethical approaches. While authoritarian management styles are adopted in countries with high power distance (e.g. China, South Korea, Türkiye), a more participatory management approach prevails in countries with low power distance (e.g. USA, Germany, Australia). Similarly, cultural dimensions such as individualism and collectivism, risk-taking capacity, and uncertainty avoidance directly affect management strategies and ethical decision-making processes. In addition, the study grouped keywords in the management, ethics, and organizational culture literature to create thematic clusters, and in this context, main research areas such as cultural diversity, ethical leadership, and digital transformation were identified. As a result, it has been understood that cultural differences play a decisive role in management approaches, ethical decision-making processes and organizational culture. Global businesses can develop more inclusive management strategies by taking cultural diversity into account and increase corporate compliance by encouraging ethical sensitivity.